2020
DOI: 10.1242/bio.048793
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of long non-coding RNA SBF2-AS1 promotes cell progression in esophageal squamous cell carcinoma (ESCC) by repressing miR-494 to up-regulate PFN2 expression

Abstract: Esophageal squamous cell carcinoma (ESCC) is an intractable esophageal cancer caused by smoking, alcohol consumption and nutritional deficiencies. Recently, long non-coding RNA SET-binding factor 2 antisense RNA 1 (SBF2-AS1) was validated as an oncogene in multiple cancers. However, the mechanism of SBF2-AS1 in ESCC progression is poorly understood. In the present research, we found that the expression of SBF2-AS1 and PFN2 was up-regulated, while miR-494 was down-regulated in ESCC tumors and cells using quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Moreover, miR-494, in the present study was found to be underexpressed while TGIF1 was overexpressed in ESCC tissues and cells. In accordance to this finding, downregulation of miR-494 has been identified in EC by multiple functional reports [ 15 , 40 , 41 ]. However, overexpression of miR-494 harbors the potential to curb the proliferative and invasive capabilities of EC cells and to trigger apoptosis by targeting CLPTM1L [ 15 ].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, miR-494, in the present study was found to be underexpressed while TGIF1 was overexpressed in ESCC tissues and cells. In accordance to this finding, downregulation of miR-494 has been identified in EC by multiple functional reports [ 15 , 40 , 41 ]. However, overexpression of miR-494 harbors the potential to curb the proliferative and invasive capabilities of EC cells and to trigger apoptosis by targeting CLPTM1L [ 15 ].…”
Section: Discussionsupporting
confidence: 77%
“…Pioneering studies demonstrated that alterations of these genes might result in tumorigenesis and development; these include SMAD5 (24,25), IL7R (26), MAP2K6 (27), and PFN2 (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In the top 20 KEGG pathways, we identified cancer-related pathways, including the TGF-β signaling pathway (involving SMAD5), the PI3K-Akt signaling pathway (involving IL7R), the Jak-STAT signaling pathway (involving IL7R), the MAPK signaling pathway (involving genes MAP2K6), the Rap1 signaling pathway (involving MAP2K6 and PFN2), and cell adhesion molecules (involving PTPRC) ( Table 2 ). Pioneering studies demonstrated that alterations of these genes might result in tumorigenesis and development; these include SMAD5 ( 24 , 25 ), IL7R ( 26 ), MAP2K6 ( 27 ), and PFN2 ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“… 21 MiR‐494‐3p has been confirmed to repress ESCC malignancy by targeting CLPTM1L 22 and PFN2. 23 Nevertheless, the function of miR‐494‐3p in the resistance of ESCC to DDP remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al manifested that downregulation of miR‐455‐3p repressed chemoresistance and tumorigenesis in ESCC 21 . MiR‐494‐3p has been confirmed to repress ESCC malignancy by targeting CLPTM1L 22 and PFN2 23 . Nevertheless, the function of miR‐494‐3p in the resistance of ESCC to DDP remains unclear.…”
Section: Introductionmentioning
confidence: 99%